What shapes yields of East African Highland banana? An explorative study from farmers’ fields - den Braber, H.; van de Ven, G.; van Heerwaarden, J.; Marinus, W.; Ronner, E.; Descheemaeker, K.; Taulya, G. (Elsevier, 2024)
Context or problem East African Highland banana is a main staple and cash crop for millions of people in the Great Lakes region of Africa. Reliable methods for banana yield estimation are lacking and factors underlying yield variability are not well understood.